Older LGBT people's experiences with healthcare professionals and services in Ireland - Mc Cann, Edward; Sheerin, Fintan; Sharek, Danika; Glacken, Michele; Higgins, Agnes (My University, 2015)
Background: The specific healthcare needs and concerns for older lesbian, gay, bisexual and transgender (LGBT) persons have not been explored to any degree within Ireland. Aims and objectives: The aim of this paper, which is part of a larger study, is to detail older LGBT persons’ usage, experiences and concerns with accessing healthcare services, disclosing their LGBT identity to professionals, preferences for care and their suggestions for improvement in services, including nursing services. Design: A mixed methods research design combining quantitative survey and qualitative interview approaches of equal significance was used. Methods: 144 respondents completed an 84‐item questionnaire concerning their use of healthcare services, experiences and needs. The qualitative phase involved in‐depth interviews where 36 participants’ experiences and concerns around health services were explored more in‐depth. Quantitative data were analysed using descriptive statistics. Qualitative analysis employed the constant comparative process to generate the leading themes. Results: Only one in three participants believed that healthcare professionals have sufficient knowledge of LGBT issues, and less than half (43%) felt respected as an LGBT person by healthcare professionals. Although 26% had chosen not to reveal their LGBT status for fear of a negative response, many positive encounters of coming out to healthcare professionals were relayed in the interviews. LGBT persons have specific concerns around residential care, particularly in relation to the perception that the Irish healthcare services emanate a heteronormative culture. Conclusions: Irish healthcare services need to reflect on how they currently engage with older LGBT persons at both an organisational and practitioner level. Consideration needs to be given to the specific concerns of ageing LGBT persons, particularly in relation to long‐term residential care. Implications for practice: Healthcare practitioners need to be knowledgeable of, and sensitive to, LGBT issues.
PUBLISHED
Keywords: LGBT; health care; long-term care; mixed methods; lesbian; gay; bisexual; transgender; Ageing; Inclusive Society